Pengembangan e-LKPD Berbasis Learning Cycle 7E untuk Menstimulus Complex Problem Solving dan Sel Efficacy Siswa - Amelia Yuni Saputri; Agus Suyatna; Abdurrahman (Postgraduate, University of Mataram, 2024)
The research conducted aims to describe e-LKPD based on the 7E learning cycle that is valid, practical, and effective in stimulating complex problem-solving (CPS) and student self-efficacy (SE). The research method used is Design and Development Research (DDR) consisting of analysis, design, development, and evaluation. After the e-LKPD was designed based on the results of an analysis of teacher and student needs, a product feasibility test was carried out with three experts and obtained valid results in aspects of media and design, content, and construction. Furthermore, the e-LKPD was tested for practicality with aspects of learning implementation, readability tests, and student responses which obtained very practical results. Furthermore, the effectiveness test using the N-Gain test, difference test, and paired test showed that there was a significant difference in the increase in CPS and SE in the experimental class and the control class and there was a significant increase in CPS and SE in the experimental class which was categorized as quite effective. Therefore, the e-LKPD based on the 7E learning cycle that has been developed has obtained valid, practical, and effective results for stimulating students' CPS and SE.